2011
DOI: 10.1007/s00268-011-1382-2
|View full text |Cite
|
Sign up to set email alerts
|

Epiploic Appendagitis: Is There Need for Surgery to Confirm Diagnosis in Spite of Clinical and Radiological Findings?

Abstract: In patients with localized abdominal pain without other symptoms, diagnosis of EA should be considered. Recognizing the US and CT features of EA may allow an accurate diagnosis and avoid unnecessary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 23 publications
(122 reference statements)
1
36
0
3
Order By: Relevance
“…Hasbahçeci ve ark. (7) tarafından 2012 yılında yayınlanan bir çalışmada, PAE tanısı almış 20 hasta geriye dönük olarak incelenmiştir. İnflame haldeki AE'nin, BT görüntülerinde kitle-lezyon ve özellikleri tanımlanarak, altı hastada Doppler USG ile santral kan akımı torsiyon açısından değerlendirilebilmiştir.…”
Section: Discussionunclassified
“…Hasbahçeci ve ark. (7) tarafından 2012 yılında yayınlanan bir çalışmada, PAE tanısı almış 20 hasta geriye dönük olarak incelenmiştir. İnflame haldeki AE'nin, BT görüntülerinde kitle-lezyon ve özellikleri tanımlanarak, altı hastada Doppler USG ile santral kan akımı torsiyon açısından değerlendirilebilmiştir.…”
Section: Discussionunclassified
“…Incidence of PEA is higher in the sigmoid colon, which is the place where appendix epiploica most commonly located [4][5][6] . Cecal PEA is seen rarely 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis of 20 patients of epiploic appendagitis, Hasbahceci et al, [5] showed that a solid oval, noncompressible hyperechoic mass with a subtle hypoechoic rim directly under the site of maximal tenderness, and lack of central blood flow on Doppler US (detected in five of six patients) is suggestive of epiploic appendagitis. They also showed that a pericolonic ovoid fatty mass with hyperattenuating rim and surrounding fat stranding is a diagnostic finding, which was present in all 20 patients of epiploic appendagitis.…”
mentioning
confidence: 97%